Pharmacological targeting of the protein synthesis mTOR/4E-BP1 pathway in cancer-associated fibroblasts abrogates pancreatic tumour chemoresistance - Duluc, Camille (EMBO Mol Med, 2015)
Pancreatic ductal adenocarcinoma (PDAC) is extremely stroma-rich. Cancer-associated fibroblasts (CAFs) secrete proteins that activate survival and promote chemoresistance of cancer cells. Our results demonstrate that CAF secretome-triggered chemoresistance is abolished upon inhibition of the protein synthesis mTOR/4E-BP1 regulatory pathway which we found highly activated in primary cultures of α-SMA-positive CAFs, isolated from human PDAC resections. CAFs selectively express the sst1 somatostatin receptor. The SOM230 analogue (Pasireotide) activates the sst1 receptor and inhibits the mTOR/4E-BP1 pathway and the resultant synthesis of secreted proteins including IL-6. Consequently, tumour growth and chemoresistance in nude mice xenografted with pancreatic cancer cells and CAFs, or with pieces of resected human PDACs, are reduced when chemotherapy (gemcitabine) is combined with SOM230 treatment. While gemcitabine alone has marginal effects, SOM230 is permissive to gemcitabine-induced cancer cell apoptosis and acts as an antifibrotic agent. We propose that selective inhibition of CAF protein synthesis with sst1-directed pharmacological compounds represents an anti-stromal-targeted therapy with promising chemosensitization potential.